Current Imaging and Therapy of Malignant Soft Tissue Tumors and Tumor-like Lesions - Beaman, Francesca D.; Jelinek, James S.; Priebat, Dennis A. (Seminars in Musculoskeletal Radiology, 2013)
Soft tissue tumors are histologically classified based on the tissue type they reflect. MR and computed tomography imaging remains the mainstay for the evaluation of a soft tissue mass including guiding the biopsy to the most aggressive portion of the lesion, tumor staging, and evaluating local recurrence and metastatic disease. Although some lesions may be readily identified based on their imaging characteristics, many soft tissue tumors remain indeterminate and require biopsy for diagnosis of histologic type and lesion grade, factors that have an impact on therapeutic options and long-term disease-free survival.In this article we review the current literature regarding imaging and treatment of soft tissue lesions in the musculoskeletal system. Positron emission tomography and specialized MR techniques, such as spectroscopy and diffusion-weighted imaging, are useful in the diagnosis of high-grade soft tissue sarcomas, although imaging overlap exists with benign and low-grade sarcomas. These modalities are proving useful in primary tumor staging, evaluation of therapeutic response, and metastatic disease assessment. We also discuss the roles of percutaneous ablation in the treatment of focal disease and palliative pain control, and review current targeted cancer therapies.
Keywords: soft tissue tumor; PET; MR imaging; percutaneous ablation; drug therapy